Effect of varying resistance exercises on the skill of smash serve in volleyball - Heider Sadiq Maki; Heider Shamkhi Jabbar; Hussein Mhaibes Tuama (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.